The Effect of Work Life Balance, Workload, and Compensation on Employee Performance with Organizational Commitment as a Moderation Variable at PT. Nusantara Plantation IV KSO Regional II Tanjung Garbus Plantation - Mira Fitriyanti; Elisabet Siahaan; Yeni Absah (Indonesian Journal Publisher, 2026)
Changes in the increasingly dynamic work environment have driven a transformation in performance management, where work life balance, workload, and compensation systems are important aspects in maintaining employee productivity. This study aims to analyze the influence of work life balance, workload, and compensation on employee performance with organizational commitment as a moderation variable in PT. Nusantara Plantation IV KSO Regional II Tanjung Garbus Plantation. Using a quantitative method with PLS-SEM analysis on 150 maintenance and harvest employee respondents selected through proportional random sampling, data were collected through a structured questionnaire. The results showed that work life balance had a positive and significant effect on employee performance (β=0.319, p=0.000), workload had a negative and significant effect on employee performance (β=-0.270, p=0.000), and compensation had a positive and significant effect on employee performance (β=0.536, p=0.000). Organizational commitment was proven to strengthen the influence of work life balance (β=0.184, p=0.011) and workload (β=0.149, p=0.009) on employee performance, but was unable to moderate the compensation relationship with employee performance (β=-0.230, p=0.001). The research model explains 80.3% variance in employee performance. These findings underscore the importance of a holistic human resource management strategy in the plantation industry, particularly in balancing productivity demands with employee well-being through effective work-life balance management, proportionate workload distribution, fair compensation systems, and strengthening organizational commitments.